2019
DOI: 10.1186/s13068-019-1528-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and mechanism of the effects of Mg–Fe layered double hydroxide nanoparticles on a marine bacterium: new insights from genomic and transcriptional analyses

Abstract: Background Layered double hydroxides (LDHs) have received widespread attention for their potential applications in catalysis, polymer nanocomposites, pharmaceuticals, and sensors. Here, the mechanism underlying the physiological effects of Mg–Fe layered double hydroxide nanoparticles on the marine bacterial species Arthrobacter oxidans KQ11 was investigated. Results Increased yields of marine dextranase (Aodex) were obtained by exposing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 66 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…Although a mutation analysis of the GOQD-exposed B. cereus was not conducted ( Mu et al, 2019 ), ENM-induced genetic mutations in bacteria have been reported. For example, the changed transcript sequence was one of the underlying mechanisms of the stimulatory effect of Mg–Fe layered double hydroxide (Mg–Fe LDH) in the marine bacterium Arthrobacter oxidans which increased its exodextranase yields upon ENM exposure ( Ren et al, 2019b ). Namely, transcriptomics revealed that exposure to Mg–Fe LDH led to formation of a new Shine-Dalgarno sequence (ribosomal binding site in bacterial messenger RNA) that influenced the expression of dextranase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a mutation analysis of the GOQD-exposed B. cereus was not conducted ( Mu et al, 2019 ), ENM-induced genetic mutations in bacteria have been reported. For example, the changed transcript sequence was one of the underlying mechanisms of the stimulatory effect of Mg–Fe layered double hydroxide (Mg–Fe LDH) in the marine bacterium Arthrobacter oxidans which increased its exodextranase yields upon ENM exposure ( Ren et al, 2019b ). Namely, transcriptomics revealed that exposure to Mg–Fe LDH led to formation of a new Shine-Dalgarno sequence (ribosomal binding site in bacterial messenger RNA) that influenced the expression of dextranase.…”
Section: Resultsmentioning
confidence: 99%
“…Fe-S clusters have been reported to be sensitive to ROS and metal ions such as copper, silver, cadmium and zinc ( Xu and Imlay, 2012 ; Vernis et al, 2017 ), which explains the dysregulation of these proteins in several studies with Ag NPs ( McQuillan and Shaw, 2014 ; Gambino et al, 2015 ) and a study involving CdTe QDs ( Aunins et al, 2019 ). Also, Mg-Fe LDHs at stimulatory concentrations were reported to downregulate the Fe-S cluster assembly ( Ren et al, 2019b ). The primary role of Fe-S clusters is electron transfer, but also transcriptional and translational regulation via sensing the changes in cellular redox conditions ( Kiley and Beinert, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the oceans, which covers more than three quarters of the Earth's surface, is an open ecosystem. It has been estimated that at least 50%, and potentially more than 90%, of all marine species are undescribed [33][34][35][36]. Marine microorganisms have been recognized as potential sources of novel enzymes with better biocatalytic properties than their terrestrial counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Marine microorganisms have been recognized as potential sources of novel enzymes with better biocatalytic properties than their terrestrial counterparts. These properties, such as salt tolerance, hyperthermostability, barophilicity, alkali-resistance, and low optimum temperatures, are necessary for e cient bioprocesses exploitation [33][34][35][36]. Hainan is a big maritime province in China and rich in marine resources, but the knowledge of cellulolytic microbes isolated from this area is limited.…”
Section: Introductionmentioning
confidence: 99%